Simulación de una cohorte de anchoa panamensis (Steindachner, 1875) en el golfo de Nicoya, Costa Rica (ING) - Palacios, José A. (1987)
Jansen´s simulation stock was applied to a hypothetical Cohort of 100.000 fishes of Anchoa panamensis using natural mortality rate (0,274) found in 1981 for a natural population and two hypothetical rates (0,35 and 0,52 month). The effect of length, weight, number of fishes and total biomass was observed.The critical age for the natural mortality of 0,27 was 6,7 months, 5,6 months for 0,35 and 4,5 months for 0,52. Both number of individuals and total biomass decreased when mortality rate increase, the first from 121.394g to 74.813g and 31.895g. The difference in fish biomass at the three mortality rate was significant. The selection factor was estimated as 5,07 for a mesh size of 13mm. Based on this a captured mesh size of 22 mm was estimated for the individuals of Ec = 6,7 months with a fish size of 113mm.